The influence of body fat percentage on physiological responses and performance in professional soccer players during a soccer game simulation protocol on a treadmill - Hadjicharalambous, M.; Apostolidis, A.; Zaras, N.; Chalari, E.; Tooba, T.; Faiz, R.; Razi, O. (Sports, 2026)
This study examined whether different body fat percentages (BF%) may influence performance, physiological responses, and fatigue in professional soccer players during a simulated soccer game protocol on a treadmill. Twenty professional male soccer players were categorized in higher (HBF%) and lower (LBF%) body fat percentage groups [HBF% > 11.5%; n = 11, BF% = 14.2 ± 2, LBM = 65.3 ± 8 kg, age = 22.7 ± 4 years, height = 177 ± 7 cm, weight = 76 ± 9 kg, VO2max = 60.1 ± 4.5]; [LBF% < 11.5%, n = 9; BF% = 8.1 ± 1, LBM = 65.9 ± 5 kg, age = 20.1 ± 3 years, height = 179 ± 4 cm, weight = 72 ± 5 kg, VO2max = 61.6 ± 4). Players underwent a simulated soccer game protocol on a treadmill. Cardiometabolic and hormonal responses, and fuel oxidation and performance, were evaluated. At baseline, apart from the BF% variable (p < 0.0001), the groups did not differ in any other physiological or physical characteristic (p > 0.05). There were no differences between the groups in any performance or biological parameters evaluated (p > 0.05), except for plasma glucose, which was higher in the HBF% group at rest and during the soccer game protocol (p < 0.05). In conclusion, the theory of a uniform ideal (~10 ± 2%) of BF% in elite soccer is not supported by the present study. This study suggests that when muscle mass and fitness levels of the soccer players are maintained at high levels during the competitive period, BF% represents a highly individualized characteristic rather than a uniform target across players. However, a higher BF% increased resting and exercising blood glucose concentrations, even in highly trained professional soccer players, without concomitant effects on metabolism or fuel oxidation during match play.